Vladimir Soloviev and the Spiritualization of Matter - Smith, Oliver (Studies in Russian and Slavic Literatures, Cultures, and History, 2010)
While he is widely acknowledged as the most important Russian thinker of the nineteenth century, Vladimir Soloviev's place in the landscape of world philosophy nevertheless remains uncertain. Approaching him through a single synoptic lens, this book foregrounds his unique envisioning of the interaction between humanity and the material world. By investigating the development of a single theme in his work-his idea of the "spiritualization of matter", the "task" of humanity-Smith constructs a rounded picture of Soloviev's overall importance to an understanding of nineteenth-century thought, as well as to modern theology and philosophy. The picture that emerges is of a writer whose contribution to a Christian philosophy of matter resonates with many of the religious debates of modernity.